Environment Education and the Ethics These Encourage A Case for Outdoor Education in the Philippines* - Mendoza, Isabella Ann (2021)
This paper discusses the role of environmental ethics and the values and motivations that can influence a person's perspective and willingness to engage in pro-environment behavior. It explores the concept of outdoor education as an experienced-based learning approach that has the potential to encourage pro-environment behavior by positively influencing the learner's relationship with nature (ecosystemic), themselves (interpersonal), their community (intrapersonal), and the impacts of human societies on the environment (ekistic). It presents the possibilities of outdoor education as a strategy for strengthening environment education and the opportunities that can be explored through pursuing this approach in the Philippine setting.
Keywords: Environmental education; Environmental ethics; Outdoor education; Outdoor recreation; Youth and the environment